Rust fungi (Pucciniales) of southern Africa - Wood, A.R. (African Biodiversity & Conservation, 2026)
The last comprehensive checklist of rust fungi (Pucciniales; Basidiomycota) of southern Africa was published in 1950 by Ethel Mary Doidge, and included 468 species. An updated listing is provided here, including all published records of rust fungi from Angola, Botswana, Eswatini (formerly Swaziland), Lesotho, Mozambique, Namibia, South Africa and Zimbabwe, and their recorded hosts. A total of 631 taxa of rust fungi are recorded, on 1 355 host plant taxa. Sphaerophragmium senegaliae A.R.Wood, Maravalia neomimusops A.R.Wood and Aecidium afrocanthii A.R.Wood are newly described. New combinations made are Milesina silvae-knysnae (R.Berndt) A.R.Wood and Elateraecium celastrineae (Cooke & Massee) A.R.Wood. Endophyllum austroafricanum (Henn.) A.R.Wood represents a new combination and has been raised to species level. Endophyllum rhamni-prinoides (Thüm.) A.R.Wood (currently known as Endophyllum macowanii Pole-Evans) and Endophyllum conyzae-scabridae A.R.Wood (currently known as Endophyllum macowanianum (Thüm.) A.R.Wood) are new names provided for species with illegitimate names.